INTRODUCTION OF THE CREDIT-MODULE SYSTEM INTO THE EDUCATIONAL PROCESS IN HIGHER EDUCATIONAL INSTITUTIONS (Web of Teachers: Inderscience Research, 2025)
This article discusses the introduction of a credit module system in higher education institutions, The issue of developing modern educational programs, raising the training of highly qualified professionals to a new level, and ensuring the harmony of education, science, and practice in the field is highlighted.